Growth, antioxidant system, and immunological status of shrimp in bioflocs and clear water culture systems - Souza, Diego Moreira de; Kutter, Mateus Tavares; Furtado, Plinio Schmidt; Romano, Luis Alberto; Wasielesky Junior, Wilson; Monserrat, José María; Garcia, Luciano (Pesquisa Agropecuaria Brasileira, 2019)
The objective of this work was to evaluate the effect of the traditional culture system in clear water and of the one in microbial flocs on the antioxidant and immunological status of Litopenaeus vannamei shrimp. Samples (gill, hemolymph, and hepatopancreas) were collected on days 15, 30, and 60 of the experimental period. The following immunological parameters were analyzed at each evaluation time: granular and hyaline hemocytes, total protein, and apoptosis. Assays on glutamate-cysteine ligase (GCL) activity and on the concentrations of reduced glutathione (GSH) and thiobarbituric acid reactive substances (TBARS) were also performed. The evaluated immunological parameters did not differ significantly between treatments. Shrimp reared in clear water showed higher levels of lipid peroxidation in the gills and of GCL activity in the hemolymph on days 15 and 30. Shrimp in microbial floc had a higher survival rate, and the water did not have to be renewed during the experimental period. The microbial floc system improves production levels and provides a healthier culture environment.